Anti-freezing performance and application of air-cooled heat exchanger with different water entry patterns. (5th January 2021) - Wang, Weijia; Wang, Fengli; Kong, Yanqiang; Yang, Lijun; Niu, Yuguang; Du, Xiaoze; Li, Ansheng
Abstract: In practical engineering, air-cooled heat exchangers are commonly equipped with middle, left, or side water entry arrangement, and in winter may be at risk for freezing. This research studies the water flow and the exit water temperature distributions of tubes in different rows and passes, and explores the anti-freezing characteristics for air-cooled heat exchangers with these three typical water entry patterns. The micro-volume transport model is adopted to more accurately determine the air/water-side thermo-flow performance of finned tubes. The results show that air-cooled heat exchangers with different water entry patterns have different water flow distributions that induce different exit water temperature distributions. However, water entry patterns have little impact on the anti-freezing performance of air-cooled heat exchangers because the minimum exit water temperature is not significantly changed. Exit water temperatures of windward row 1 tubes, especially those near the header region of an air-cooled heat exchanger with a middle-type header and far from the header region of an air-cooled heat exchanger with a left/side header, are suggested for monitoring at dry-cooling power plants.